A comparison of intertidal species richness and composition between Central California and Oahu, Hawaii. (15th October 2012) - Zabin, Chela J.; Danner, Eric M.; Baumgartner, Erin P.; Spafford, David; Miller, Kathy Ann; Pearse, John S.
Abstract: The intertidal zone of tropical islands is particularly poorly known. In contrast, temperate locations such as California's Monterey Bay are fairly well studied. However, even in these locations, studies have tended to focus on a few species or locations. Here we present the results of the first broadscale surveys of invertebrate, fish and algal species richness from a tropical island, Oahu, Hawaii, and a temperate mainland coast, Central California. Data were gathered through surveys of 10 sites in the early 1970s and again in the mid‐1990s in San Mateo and Santa Cruz counties, California, and of nine sites in 2001–2005 on Oahu. Surveys were conducted in a similar manner allowing for a comparison between Oahu and Central California and, for California, a comparison between time periods 24 years apart. We report a previously undocumented richness of intertidal species in both locations: 516 for Oahu and 801 for Central California. Surprisingly, when differences in search efforts are controlled, overall (alpha) diversity appears to be similar between locations, although site level (beta) diversity is much higher in California. Species richness in California generally increased along a wave exposure gradient and distance from an urban area. Much higher numbers of both invasive and endemic species were found on Oahu. In California, more invertebrate species were found in the 1990s, likely due to an improvement in taxonomic resources since the 1970s, and species composition was different in the two surveys due to the high incidence of rare species. Although some southern species increased in number between the two time periods and some northern species decreased, we detected little evidence of change favoring southern or northern species. These results are in line with recent findings that water temperatures in the Monterey Bay have been in a cooling trend since the 1980s, in contrast to many locations elsewhere in the world.